2010
DOI: 10.1002/ceat.200900534
|View full text |Cite
|
Sign up to set email alerts
|

DNA Depletion by Precipitation in the Purification of Cell Culture‐Derived Influenza Vaccines

Abstract: A pilot study for the purification of cell culture-derived human influenza virus is presented, which focuses on the early removal of DNA by precipitation. Strains of influenza virus were propagated using Madin Darby canine kidney cells as a host. A harvesting time of about 72 h postinfection was chosen to minimize the level of impurities (host cell DNA and protein). Cell culture supernatant was clarified by centrifugation and the performance of this operation was characterized on the basis of Sigma theory. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…For example, it was demonstrated that fine adjustment of the precipitant concentration enables up to 90% DNA removal with more than 90% adenovirus recovery (Goerke et al, ). Kröber et al () implemented a DNA precipitation method for influenza vaccine: polyethyleneimine (PEI) was used, and the optimal conditions were obtained through a DoE approach achieving 85% DNA removal. Selective DNA precipitation has the advantage of being inexpensive, easily scalable—precipitated DNA can be removed by depth filtration—and suitable for high cell density processes.…”
Section: Harvestmentioning
confidence: 99%
“…For example, it was demonstrated that fine adjustment of the precipitant concentration enables up to 90% DNA removal with more than 90% adenovirus recovery (Goerke et al, ). Kröber et al () implemented a DNA precipitation method for influenza vaccine: polyethyleneimine (PEI) was used, and the optimal conditions were obtained through a DoE approach achieving 85% DNA removal. Selective DNA precipitation has the advantage of being inexpensive, easily scalable—precipitated DNA can be removed by depth filtration—and suitable for high cell density processes.…”
Section: Harvestmentioning
confidence: 99%
“…Purification studies have been conducted which demonstrate the utility of precipitation compared to centrifugation for viral vectors such as bovine rotavirus and AAV [78]. In addition, rather than precipitating the virus itself, some researchers have instead precipitated host cell proteins and nucleic acids [75,79]. Like the commonly-used CsCl 2 centrifugation method, however, precipitation may also reduce phage activity (measured in PFU/mL) [74].…”
Section: Crude Lysate Treatmentsmentioning
confidence: 99%
“…Like the commonly-used CsCl 2 centrifugation method, however, precipitation may also reduce phage activity (measured in PFU/mL) [74]. Another potential drawback of precipitation was elucidated in the Kröber et al study with influenza viruses, which found that the isoelectric point of the particles contributed to product losses by co-precipitation with cationic polymers [75,79]. Precipitation may be improved for utility with phages by enhancing process robustness and identifying nontoxic compounds to be applied in pharmaceutical production [75].…”
Section: Crude Lysate Treatmentsmentioning
confidence: 99%